Mythologizing Mortis: The Clone Wars as Dialogic Spirituality - Sweet, Derek (Journal of religion and popular culture, 2019)
This article explores the Mortis trilogy, a three-episode story arc from the third season of Star Wars: The Clone Wars, as the rhetorical articulation of a spiritual text. As more than one Star Wars scholar has pointed out, some fans draw on the spiritual ideologies scattered throughout the popular franchise and position themselves as real-life followers of a Jedi code. With this in mind, I suggest that the Mortis story arc offers a lucid account of the Force as related to spiritual practice. As Scott Stroud points out in his work examining the intersection of popular culture, rhetoric, and religion, spiritual texts serve two primary functions: (1) to explain the divine nature of the world and (2) to offer the means to achieve spiritual awareness. I contend that the Mortis trilogy fulfills both of these functions. To make my argument concerning The Clone Wars story arc explicit, I explore the relationship between Star Wars and spiritual practice, emphasize the rhetorical nature of such a relationship, and illustrate how the Mortis trilogy offers a coherent spirituality lacking in the other texts of the Star Wars universe.